2016
DOI: 10.5137/1019-5149.jtn.17432-16.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects and mechanism of the curcumin with different acting drugs in experimental vasospasm after subarachnoid hemorrhage

Abstract: ABSTRACTexperimental and clinical studies, the exact underlying mechanisms for the associated pathological conditions such as vasospasm remain to be identified. Major histological change during the cerebral vasospasm after SAH is the endothelial cell injury induced by apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Similar improvements in the rate of vasospasm were seen in a recent study comparing the actions of nimodipine, nicorandil, and low and high-dose curcumin on cerebral vasospasm. This demonstrated that high-dose curcumin is associated with a lower rate of vasospasm compared to nimodipine and nicorandil [166]. Unfortunately, this study did not perform any behavioural testing.…”
Section: Sulforaphanementioning
confidence: 99%
“…Similar improvements in the rate of vasospasm were seen in a recent study comparing the actions of nimodipine, nicorandil, and low and high-dose curcumin on cerebral vasospasm. This demonstrated that high-dose curcumin is associated with a lower rate of vasospasm compared to nimodipine and nicorandil [166]. Unfortunately, this study did not perform any behavioural testing.…”
Section: Sulforaphanementioning
confidence: 99%